Market Conditions and Speed of Innovation on Increasing Sales of Micro and Small Entrepreneurs in Ternate City - Marwan Man Soleman; Rahmat Sabuhari; Ruslan A. Kamis (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sumatera Utara, 2023)
The decline in people's purchasing power can be caused by market conditions, which of course, has an impact on decreasing the income of Micro and Small Enterprises (MSE) actors. This research was conducted to determine the ability to understand market conditions and the speed of innovation of MSME entrepreneurs toward increasing their sales in the City of Ternate. Research data was collected through a questionnaire on MSE actors in 5 sub-districts across Ternate. A total of 339 questionnaires were collected. Research data were analyzed using SEM-PLS analysis. The results show that market conditions and the speed of innovation directly affect the increase in sales. The level of innovation can mediate the influence of market conditions on sales. This finding has implications for MSEs to have the ability to understand market conditions and the pace of innovation in managing their business amid rapidly changing market conditions. Another interest for the Regional Government of the City of Ternate is to conduct training and policy assistance related to very rapid changes in market conditions due to changes in consumer tastes.